Wanderings of hobo: a transposon in Drosophila melanogaster and its close relatives. - Boussy, I.A.; Itoh, M. (Genetica, 2004)
The transposon hobo is present in the genomes of Drosophila melanogaster and Drosophila simulans (and D. mauritiana and probably D. sechellia, based on Southern blots) as full-size elements and internally deleted copies. The full-size melanogaster, simulans and mauritiana hobo elements are 99.9% identical at the DNA sequence level, and internally deleted copies in these species essentially differ only in having deletions. In addition to these, hobo-related sequences are present and detectable with a hobo probe in all these species. Those in D. melanogaster are 86-94% identical to the canonical hobo, but with many indels. We have sequenced one that appears to be inserted in heterochromatin (GenBank Acc. No. AF520587). It is 87.6% identical to the canonical hobo, but quite fragmented by indels, with remnants of other transposons inserted in and near it, and clearly is defunct. Numerous similar elements are found in the sequenced D. melanogaster genome. It has recently been shown that some are fixed in the euchromatic genome, but it is probable that still more reside in heterochromatic regions not included in the D. melanogaster genome database. They are probably all relics of an earlier introduction of hobo into the ancestral species. There appear to have been a minimum of two introductions of hobo into the melanogaster subgroup, and more likely three, two ancient and one quite recent. The recent introduction of hobo was probably followed by transfers between the extant species (whether 'horizontally' or by infrequent interspecific hybridization).